Non-Alcoholic Fatty Liver Disease (NAFLD) Is it an Emerging Risk Factor for Coronary Artery Disease? - Shrestha, Umar Kumar (Journal of Advances in Internal Medicine, 2012)
DOI: http://dx.doi.org/10.3126/jaim.v1i1.5780 Keywords: coronary artery disease; non alcoholic - fatty liver; disease; metabolic syndrome Journal of Advances in Internal Medicine. 2012;01(1)1-2.